2015
DOI: 10.1038/srep10588
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the limits of radiofrequency (RF) neuronal telemetry

Abstract: In a previous report it was shown that the channel capacity of an in vivo communication link using microscopic antennas at radiofrequency is severely limited by the requirement not to damage the tissue surrounding the antennas. For dipole-like antennas the strong electric field dissipates too much power into body tissues. Loop-type antennas have a strong magnetic near field and so dissipate much less power into the surrounding tissues but they require such a large current that the antenna temperature is raised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Moreover, the electrical engineering community have also shown that the dual of Maxwell's equation may be excited by non-conservative electromagnetic systems or voltage generators [1][2][3], without the need for monopoles to exist. Thus, from two-potential theory, and given there is no magnetic scalar field in the system we are describing, we may write the potential of the defined fields in Equations ( 3)- (11) as…”
Section: Quasi-static Time Dependent Active Hertzian Dipole; Fields A...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the electrical engineering community have also shown that the dual of Maxwell's equation may be excited by non-conservative electromagnetic systems or voltage generators [1][2][3], without the need for monopoles to exist. Thus, from two-potential theory, and given there is no magnetic scalar field in the system we are describing, we may write the potential of the defined fields in Equations ( 3)- (11) as…”
Section: Quasi-static Time Dependent Active Hertzian Dipole; Fields A...mentioning
confidence: 99%
“…Inside the active dipole, the polarisation field, P i e , exists without any applied electric field, with both vector and scalar potential components, with the scalar component exactly equal and opposite to the scalar potential of the E field, consistent with Equation (3). Meanwhile, E i e and E T have the same vector curl and thus the same component of electric vector potential, while satisfying the constitutive given by Equation (11).…”
Section: Quasi-static Time Dependent Active Hertzian Dipole; Fields A...mentioning
confidence: 99%
See 1 more Smart Citation
“…The loop antenna has an intense magnetic near-field which dissipates much less power to the surrounding tissues than the dipole antennas with a strong electric field. Thus a small loop antenna results in better efficiency in the biological tissues [29]. The reason for improved efficiency with the loop antennas is the magnetic permeability of the biological tissues that is lossless (µr=1).…”
Section: Implant Antenna Designmentioning
confidence: 99%